2011
DOI: 10.4291/wjgp.v2.i6.88
|View full text |Cite
|
Sign up to set email alerts
|

Adenomyoma of the small intestine

Abstract: Adenomyoma of the gastrointestinal tract is a rare benign tumor-like lesion. The small intestine is the second most frequent location, usually in the periampullary area, but the lesion also occurs in the jejunum and ileum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 25 publications
0
31
0
1
Order By: Relevance
“…An adenomyoma of the gastrointestinal tract, also referred to as a myoepithelial hamartoma, adenomyomatous hamartoma, or foregut choristoma, is a benign tumor‐like lesion that develops during the embryonic stage . Histopathologically, adenomyoma are characterized by glandular structures lined by cuboidal to tall columnar epithelium and surrounded by bundles of smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…An adenomyoma of the gastrointestinal tract, also referred to as a myoepithelial hamartoma, adenomyomatous hamartoma, or foregut choristoma, is a benign tumor‐like lesion that develops during the embryonic stage . Histopathologically, adenomyoma are characterized by glandular structures lined by cuboidal to tall columnar epithelium and surrounded by bundles of smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…5 While the incidence of small intestine adenomyoma is relatively rare, the actual incidence is unclear because very few cases have been reported. Review of the literature reveals 34 reported cases in the small intestine, 3,[5][6][7][8][9][10][11][12][13][15][16][17][18][19][20][21][23][24][25][26][27][28][29][30][31][32][33][34] including the duodenum, ampulla of Vater, and ileum, with 11 well-documented cases reported in the jejunum (Table 1). 3,5,9-10,16-17, 20-21,29,31,34 Of these cases, the patients were between the ages of three to eighty one years old, with six women and five men.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of adenomyoma remains unclear, but the most widely accepted hypothesis is that it represents either a form of myoepithelialhamartoma or pancreatic heterotopia. 26 The term 'hamartoma' refers to a focal but excessive overgrowth of cells indigenous to the particular site, while the term 'heterotopia' refers to microscopically normal cells that are present in an abnormal location. Clarke suggested that the classification of 'adenomyoma' be used only for lesions with exocrine-type ducts without ectopic pancreatic acini or islets surrounded by smooth muscle, and that the term 'pancreatic heterotopia' should refer to lesions with ectopic pancreatic acini or islets.…”
Section: Discussionmentioning
confidence: 99%
“…Adenomyoma of the gastrointestinal tract was first described in the stomach by Magnus‐Alsleben in 1903 .The actual incidence remains unclear, because very few cases have been reported since then. Most common sites involved in the gastrointestinal tract are the gallbladder and the biliary tree .…”
Section: Discussionmentioning
confidence: 99%